VIOLÊNCIAS NAS ESCOLAS E REPRESENTAÇÕES SOCIAIS: um diálogo necessário no cotidiano escolar - Ana Maria Eyng (Revista Diálogo Educacional, 2009)
The social representations include historical, social and cultural dimensions that emerge in the decision making and in the everyday actions of the schools. Therefore, to understand the representations of the several actors in/of the school context as dimensions of the complexity of the school phenomena, means to understand the school in its complexity. Under this perspective, the representations of violence that manifest everyday in the school, aim to provide a better understanding of that phenomena and create strategies to reduce and prevent it. The research was developed in two phases, the first one in 2006 and 2007, with 728 students of basic education and high school, and 57 teachers in seven public schools of the Paraná State, using the evocation technique. The second phase in 2008, in a big public state school, was developed with parents, students and teachers, administrative and pedagogical professionals - grouped up as staff, through structured interviews. The data obtained show that the phenomena of violence in schools is understood differently by the several actors, what might be associated to the fact that this phenomena, was not constituted, in general terms, in a question of collective analysis and proposal of group actions. Considering that the social representations are strongly related to the beliefs of each social group and of its context, it is important to highlight the necessity to go deeper into the collective discussion, to define positions and strategies of shared actions, specially, the insertion of this theme in the courses of initial and continuous formation of teachers for basic education.